Exploring Compassionate Care in Virtual Rehabilitation: Qualitative Study - Parminder Flora; Angela Tobia; Lee Verweel; Bernice Lau; Janet Campbell; Arezoo Eshraghi; Steven Dilkas; Roger Goldstein; Patricia Raulino; Crystal MacKay (JMIR Rehabilitation and Assistive Technologies)
Abstract BackgroundVirtually delivered health care services can offer numerous benefits, and the demand for virtual care continues to grow among subgroups facing mobility challenges. The experience of compassion in health care is linked to patient satisfaction and clinical outcomes; however, this link in virtual rehabilitation settings is underexplored. ObjectiveThe objectives of this study were to explore what compassionate care means to rehabilitation patients in a virtual rehabilitation context and explore patients’ experiences of how the technology associated with virtual rehabilitation impacted their experience of care. MethodsWe conducted one-on-one semistructured qualitative interviews with patients with limb loss and chronic obstructive pulmonary disease. A reflexive thematic analysis approach was used to generate domain summaries and initial themes across the sample. Themes were generated following analytic work over a series of discussions within the research team. ResultsSixteen interviews were conducted. Four themes illustrating participants’ perceptions of compassionate care were generated: (1) features of compassionate care include feeling valued, connected, and cared for by the health care provider; (2) threats to compassionate care in virtual rehabilitation; (3) facilitating compassion in virtual rehabilitation through preparation; and (4) benefits of virtual care. ConclusionsPatient perceptions of compassionate care in a virtual rehabilitation setting may be impacted by the behaviors and communication of providers. Provider training and preparation and the personal connections formed with their patients may impact compassionate care experiences.